Opioid Alternatives in Spine Surgery: A Narrative Review. Issue 1 (January 2022) - Rajan, Shobana; Devarajan, Jagan; Krishnaney, Ajit; George, Arun; Rasouli, Jonathan J.; Avitsian, Rafi
Abstract : Adequate analgesia is known to improve outcomes after spine surgery. Despite recent attention highlighting the negative effects of narcotics and their addiction potential, opioids have been the mainstay of management for providing analgesia following spine surgeries. However, side effects including hyperalgesia, tolerance, and subsequent dependence restrict the generous usage of opioids. Multimodal analgesia regimens acting through different mechanisms offer significant opioid sparing and minimize the side effects of individual drugs. Hence, they are being increasingly incorporated into enhanced recovery protocols. Multimodal analgesia includes drugs such as N-methyl-D-aspartate antagonists, nonsteroidal anti-inflammatory drugs and membrane-stabilizing agents, neuraxial opioids, local anesthetic infiltration, and fascial compartment blocks. Analgesia started before the painful stimulus, termed preemptive analgesia, facilitates subsequent pain management. Both nonsteroidal anti-inflammatory drugs and neuraxial analgesia have been conclusively shown to reduce opioid requirements after spine surgery, and there is a resurgence of interest in the use of low-dose ketamine or methadone. Neuraxial narcotics offer enhanced analgesia for a longer duration with lower dosage and side effect profiles compared with systemic opioid administration. Fascial compartment blocks are increasingly used as they provide effective analgesia with fewer adverse effects. In this narrative review, we will discuss multimodality analgesic regimens incorporating opioid-sparing adjuvants to manage pain after spine surgery. Abstract : Supplemental Digital Content is available in the text.